CYTOGENETICAL STUDY IN SOME ALFALFA CULTIVARS OF IRAN (Journal of Sciences, Islamic Republic of Iran)
A cytogenetical study on 13 alfalfa (Medicago sativa) cultivars available in Iranian Forest and Rangelands Genebank was performed in order to obtain basic information on the variability in chiasma frequency/distribution, chromosome association and segregation. Such cytogenetic information is useful for planning hybridization programs. Cluster analysis of meiotic data and ordination of cultivars based on the first two principal component axes (PCA) grouped the genotypes with similar meiotic characteristics. PCA analysis of meiotic data revealed that the mean total chiasma, mean terminal chiasma, ring and rod bivalents are the most variable meiotic characteristics among the genotypes studied. Pollen fertility was studied in all genotypes that showed a significant positive correlation with the frequency of terminal and total chiasma as well as proper segregation of chromosomes during anaphase and telophase stages. B-chromosomes were observed in some of the cultivars affecting the chiasma frequency/distribution as well as chromosome association.